The management of projects - Morris, Peter W.G (T. Telford, 1994)
This book will undoubtedly become one of the classics of the project management literature...There will be a growing need for project managers who can look beyond the internal processes of their projects to the organisational, technological and socio-economic contexts in which projects must be managed. A good starting point would be for all project managers to read this...book.'- Construction Management and Economics